The role of accounting standards, audit and finances in control On agricultural activity to achieve sustainable development (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The agricultural activity has a great significance in the all four dimensions of sustainable development. Firstly, the economic dimension which it contributes with the GDP, as well as, it is considered as an important source to attract the investment. Secondly, the environmental dimension which also contributes with conserving of the biodiversity, combating the desertification, and increasing the farmlands. Thirdly, for its role in the social dimension to achieve the food security, to eradicate the poverty, and providing jobs. Fourthly, toward the institutional dimension as well it is considered as a source that allows all people to participate effectively, and to exchange of the local and universal experiences and perspectives. For confronting of the challenges which are presented of the failure many projects of agricultural activity, and the misusing of devoted funds of supporting the agricultural activity, which led to the weakening of the role of agricultural activity in sustainable development. The research sought to embodies the criteria of accounting and audit , as well as the criteria of the financial funding in the censorship of agricultural activity to achieve the goals of sustainable development according to its dimensions. One of the most important conclusions, is that existence of the criteria of accounting and auditing, as well as criteria which concern with environmental and social sustainability, which are not employed at the censorship on the agricultural activity. To sum up, to achieve sustainable development, the research paper has recommended on the necessity of embodying those criteria when conducting censorship on the projects of agricultural activity, to achieve the aims of sustainable development.